The haplotypes distribution, reproductive mode differentiation and related symbiotic bacteria analysis in Aphis gossypii from diverse hosts in Yangtze river basin in China - Liu, Zhe; Fang, Xiaoyun; Askar, Mofeed; Su, Honghua; Jing, Tianxing; Zhang, Shuai; Yang, Yizhong (Frontiers in Ecology and Evolution, 2024)
The cotton-melon aphid (Aphis gossypii) is a globally distributed species with highly differentiated populations and various life cycle types. Based on the haplotype classification of the A. gossypii, this study aimed to quantify the effects of latitude, host specialization on transformation of the sexual morph of the A. gossypii. Additionally, symbiotic bacteria potentially involved in the formation of sexual morph were investigated. The results showed that I):The most frequent haplotypes on the 29 host plants were Hap1 (60.42%), Hap17 (13.29%), and Hap4 (7.55%). Haplotypes in cotton fields of 10 geographic populations were predominantly Hap1 and Hap4. II):A. gossypii from the Northwestern inland, the Yellow River basin, and the Yangtze River basin cotton regions all were induced sexual morphs, except for Hap1 from low latitudes. There are also differences in the efficiency of sex aphid induction between haplotypes under the same region/latitude(Jiangsu Yangzhou), which can be corresponded to three life cycle types: holocyclic (Hap1 and Hap4), facultative (Hap17 and Hap1-1), and specialized parthenogenetic (Hap3 and Hap16) life cycle. Interestingly, sexual morphogenesis of A. gossypii with facultative life cycle are more susceptible influenced by the host. Subsequent field surveys in Yangzhou, Jiangsu have also confirmed that the haplotypes capable of sexual morphology transformation under natural rhythm variations are Hap1 and Hap4. It is worth mentioning that these sexual aphids are mainly distributed on some Malvaceae plants, Chinese prickly ash, and pomegranate. However, aphids with specialized parthenogenetic life cycle can complete their entire life history by overwintering on crops or weeds (such as capsella and veronica) in greenhouses or outdoors. III):The relative abundance of Arsenophonus, Pantoea and Enterobacter varied among haplotypes. In particular. the relative abundance of Arsenophonus was generally higher in holocyclic aphids than in anholocyclic aphids in the parthenogenetic morphology. Additionally, Arsenophonus higher in gynoparas and females than in males in the sexual morphology. It can be observed that the aforementioned symbiotic bacteria may play a role in the development of the specialized or reproductive mode of the A. gossypii. The present study contributes to our understanding of the ecological adaptations of the A. gossypii to different climatic conditions and host plants. Moreover, it will furnish a crucial foundation for unravelling the diversification of reproductive modes exhibited by A. gossypii.